Value Creation Through Acquisition Strategy: A Study Of Volvoâs Acquisition By Geely - Handyanto Widjojo, Yane Chandera, (INTERNATIONAL RESEARCH JOURNAL OF BUSINESS STUDIES, 2012)
This paper examines the value creation on the acquisition of Volvo Car Corp by Zhejiang Geely Holding Group. The acquisition of Volvo by Geely became an interesting topic to discuss since it was the first time in automotive industry that a Chinese company acquired an international company with a considerably high transaction amount. The paper examines the short term value creation using event study to calculate abnormal returns of each companyâs stock during the announcement period and measuring the significance of the cumulative abnormal return. The findings are consistent with previous studies over the years which have shown that most acquisitions fail to add value for shareholders in the acquiring company. The paper discusses the broad managerial implications of the findings this paper discussion on marketing aspect after the acquisition by integrating two different brand perceptions.DOI :Â https://doi.org/10.21632/irjbs.5.2.129-143Keywords: value creation, acquisition, Geely, Volvo, automotive, China, event study, abnormal return, cumulative abnormal return, management, brand perception, cross border transaction